STRENGTH TRAINING ANATOMY FOR ATHLETES - Delavier, Frédéric; Gundill, Michael (Human Kinetics, 2019)
With over 600 full-color photos and 300 anatomical illustrations, you'll be taken inside 46 exercises specifically selected for the demands of 43 sports and activities. You'll see how muscles interact with surrounding joints and skeletal structures and how variations and sequencing can isolate specific muscles for more effective and efficient training. Strength Training Anatomy for Athletes guides you in analyzing the needs of your sport and identifying the most effective exercises for your body type, physical conditioning, and performance goals. You'll enhance your strengths and minimize your weaknesses with programs for 43 sports and activities, including these Archery, Basketball, Baseball and softball, Combat sports, Cycling, Football, Golf, Rugby, Soccer, Swimming and diving, Tennis, Volleyball. Featuring exercises for warm-up, recovery, and injury prevention, Strength Training Anatomy for Athletes is a comprehensive, yet practical, guide to optimizing athletic performance.